Sharing notes with patients: A review of current practice and considerations for neurologists - Yu, Melissa M. (Neurol Clin Pract, 2017)
Improved patient engagement is a critical consideration in the new payment climate. Releasing progress notes for patients to view may improve patient involvement and engagement in their care. Patients perceive benefit from viewing physician progress notes. As initial studies involved only primary care physicians, specialist physicians may have specific considerations when releasing notes to patients. This article provides a framework for neurologists to implement a note release policy in their practice.